The Jokowi’s Ideology Reflected on the Annual Speech - Muhammad Muqoffa; Nurul Chojimah; Ika Nurhayani (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2019)
This study aimed to find out the ideology of Jokowi as the seventh president of Indonesia. It followed Fairclough’s framework of critical discourse analysis and Searle’s speech act as analysis tool. The data source of the study involved two Joko Widodo’s speech in the Annual session of the people's Consultative Assembly. Moreover, the main data of the study are the utterances from Joko Widodo’s speech which contain an illocutionary act. The result of this study showed four types of illocutionary act employed by Joko Widodo; they were representatives, directives, commisives, expressives. The representatives were mostly reflected in the speech. This study found that Jokowi expressed his alignment toward the high state institutions.